ISLAMIC VALUES IN THE DOI 'MENRE TRADITION IN THE BUGIS TRADITIONAL MARRIAGE OF TERUJUNG DUSUN, LABUAN AJI VILLAGE, TARANO DISTRICT SUMBAWA DISTRICT - nur azisa (JOETAL: Journal of Education, Teaching and Learning, 2024)
The values ​​of Islamic education can be sought in many ways, one of which is in tradition, especially in the traditions that exist in Indonesia. This education aims to find out the values ​​of doi menre and the focus studied in this thesis is (1) The process of implementing the Doi'menre tradition or gift money in traditional Bugis marriages. (2) The values ​​of Islamic education contained in the Doi' Menre tradition. This research aims to determine the values ​​of Islamic education in the Doi' Menre' tradition in Bugis traditional marriages in Terujung Hamlet, Labuan Aji Village, Tarano District, Sumbawa Regency. This research is qualitative research with a descriptive approach, because it can describe the values ​​and stages in implementing the doi menre tradition. Data collection was carried out using observation, interviews and documentation methods. The data analysis techniques used are data reduction, data presentation, and drawing conclusions.  The results of research in the field show that there are ten processes in implementing the Doi'menre tradition, namely the exploration stage (mapesek-pesek), madduta, mappatettong serapo, mette, mappaisseng, mappassau botting, mappanre temme, mappacci, ipanikka, and the final process of mellau dampeng. Then there are five Islamic values ​​in the Doi Menre tradition, namely the value of respect for women, the value of mutual cooperation, social values, the value of knowledge, and the last value, namely spiritual values.